Prognostic Value of the 13C‐Methacetin Breath Test in Adults with Acute Liver Failure and Non‐acetaminophen Acute Liver Injury. Issue 2 (26th August 2021) - Fontana, Robert J.; Stravitz, R. Todd; Durkalski, Valerie; Hanje, James; Hameed, Bilal; Koch, David; Reuben, Adrian; Ganger, Daniel; Olson, Jody; Liou, Iris; McGuire, Brendan M.; Clasen, Kristen; et al.
Abstract : Background and Aims: The 13 C‐methacetin breath test (MBT) is a noninvasive, quantitative hepatic metabolic function test. The aim of this prospective, multicenter study was to determine the utility of initial and serial 13 C‐MBT in predicting 21‐day outcomes in adults with acute liver failure (ALF) and non‐acetaminophen acute liver injury (ALI). Approach and Results: The 13 C‐MBT BreathID device (Exalenz Biosciences, Ltd.) provided the percent dose recovery (PDR) for a duration of 60 minutes after administration of 13 C‐methacetin solution as the change in exhaled 13 CO2 / 12 CO2 compared with pre‐ingestion ratio on study days 1, 2, 3, 5, and 7. Results were correlated with 21‐day transplant‐free survival and other prognostic indices. A total of 280 subjects were screened for enrollment between May 2016 and August 2019. Median age of the 62 enrolled patients with adequate data was 43 years, 79% were Caucasian, 76% had ALF with the remaining 24% having ALI. The mean PDR peak on day 1 or day 2 was significantly lower in nonsurvivors compared with transplant‐free survivors (2.3%/hour vs. 9.1%/hour; P  < 0.0001). In addition, serial PDR peaks were consistently lower in nonsurvivors versus survivors ( P  < 0.0001). The area under the receiver operating characteristic curve (AUROC) of the 13 C‐MBT in the combined cohort was 0.88 (95% CI: 0.79‐0.97) and higher than that provided by King's College (AUROC = 0.70) and Model for End‐Stage Liver Disease scores (AUROC = 0.83). The 13 C‐MBT was well tolerated with only two gastrointestinal adverse events reported. Conclusions: The 13 C‐MBT is a promising tool to estimate the likelihood of hepatic recovery in patients with ALF and ALI. Use of the PDR peak data from the 13 C‐MBT point‐of‐care test may assist with medical decision making and help avoid unnecessary transplantation in critically ill patients with ALF and ALI.